Hegemony, Resistance, and Destabilization of Meaning: Study of the Horeg Sound Fatwa through Ernesto Laclau's Post-Sructuralist Analysis - Ahmad Irfan Fauzi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This article examines the contestation of horeg sound meaning through Ernesto Laclau's post-structuralist discourse analysis approach. This study places the Indonesian Ulema Council (MUI) Fatwa of East Java Number 1 of 2025 concerning the use of horeg sound as a nodal point in discourse analysis. This research is conceptually-empirically based with qualitative methods that combine document studies and digital observations of the fatwa text, media coverage, and social media. Data analysis is conducted through three dimensions of post-structuralist discourse analysis, namely; articulation, hegemony, and repositioning of meaning by exploring the relations of equivalence and differentiation between symbols. This analysis positions the fatwa prohibiting horeg sound not to be interpreted simply as a matter of religious law, but this phenomenon reflects the discursive struggle between religious authorities and popular culture. The fatwa functions as an instrument of hegemony of meaning, in which religious authorities attempt to assert moral dominance by categorizing horeg sound as a negative practice articulated with disturbance and haram. This hegemonic effort sparked social resistance, particularly from young people who resorted to symbolic repositioning through the term "carnival sound" as a form of symbolic resistance to religious authority. The research results show that the fatwa actually destabilized meaning and opened up new spaces for contestation within the field of discursivity. This confirms that religious discourse is contingent, fragile, and always open to negotiation of meaning and social resistance.